تعليم قراءة الكتب باستخدام النصوص العربية لترقية مهارة القراءة لدى طالبات المرحلة الثانوية بمعهد دار العلوم موارامايس جمبور - Nur Hidayah; Syaipuddin Ritonga; Ria Rafita Supriani (Jurnal Pendidikan dan Humaniora Rumbio, 2025)
The objectives of this study include students' mastery of Arabic language text reading books used in secondary schools at the Dar Al-Ulum Institute, techniques used in teaching reading books, and challenges and expectations in teaching reading books in secondary schools at the Dar Al-Ulum Institute. The results of this study produce three conclusions: teaching reading books at the secondary school level at the Darul Uloom Moramais Institute is not found in certain places because of the many books used along with Arabic texts, and teaching reading books is adequate. As for the challenges and expectations in reading books at the secondary school level at the Darul Uloom Institute, both are motivating factors or inhibiting factors. Factors driving improved reading skills include teacher enthusiasm in teaching Arabic texts, the availability of learning resources that support and facilitate learning, and independent learning activities. A holy book reading competition is held annually at this institution. Factors contributing to students' lack of interest in learning to read include some students' weakness in reading Arabic texts and the Quran due to their lack of fluency in reading, difficulties in pronouncing letters when learning to read Arabic texts, and a significant number of students' tendency to be lazy in paying attention during class. The techniques used at the secondary level at this institution vary by lecturer, including the primary method of determining the type of textbook for each course. Most teachers employ a tiered approach, including lectures, memorization, and the method of reading books effectively.